Pengaruh Service Recovery Dan Service Quality Terhadap Customer Satisfaction (Studi Kasus di UMKM Griya Laudry) - Nindy Sagrya Almenia; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of Service Recovery and Service Quality on Customer Satisfaction. A case study of Griya Laundry UMKM. This research was conducted at the Griya Laundry UMKM in Kasembon District. This research is included in the type of explanatory research where this research uses a quantitative approach. The population in this study were consumers who were at least 17 years old, had experienced Service Failures and had made transactions at the Griya Laundry UMKM, while the sample studied was 60 respondents. Data collection techniques using a questionnaire. Sources of data in this study using primary data. The data was processed using SPSS 14.0 software. The data analysis method used is an instrument test consisting of validity test, reliability test then normality test, classical assumption test, hypothesis test consisting of f test, t test and determination test. It is known that the f test shows that Service Recovery and Service Quality have a simultaneous effect on Customer Satisfaction. while the t test shows that Service Recovery has a positive and significant effect on Customer Satisfaction. Service Quality has a positive and significant effect on Customer Satisfaction. In the Adjusted R Square coefficient of determination, the results show 69.5% and another 30.5% is influenced by other factors not included in the study. Keywords: Service Recovery, Service Quality, Customer Satisfation